Effect of the Dynamic Cone Angle on the Atomization Performance of a Piezoceramic Vibrating Mesh Atomizer - Qiufeng Yan; Chuanyu Wu; Jianhui Zhang (Applied Sciences, 2019)
In this paper, we find that the dynamic cone angle of a piezoceramic atomizer is linked to periodic changes in the volume of the micro-cone hole of the atomizer, and such changes affect atomization performance. Firstly, we explained the theory of the dynamic cone angle inside the vibrating mesh atomizer. Then, we analyzed the flow status of liquid in the micro-cone hole, and the one-way flow Rof the liquid is caused by the difference of diffuser and nozzle flow resistance. The volume change of the micro-cone hole and the liquid chamber can produce atomization. Furthermore, we developed the experiment to measure the atomization rate, atomization height, and the diameter of the atomized particles. The experiments reveal that the atomization rate and height are much larger when the vibrating mesh atomizer is working in the forward path than in the reverse one. The atomization rate and atomization height increase as the working voltage increases. Meanwhile, with increasing driving voltage to the piezoceramic actuator, the atomization particle size decrease and the atomized particle size distribution is more concentrated. Finally, the size of the micro-cone hole was measured using a microscope with different direct current (DC) voltages, further demonstrating the existence of the dynamic cone angle.